PENENTUAN DOSIS MINIMUM EKSTRAK ETANOL HERBA KROKOT (Portulaca oleracea L.) TERHADAP PENURUNAN KADAR TRIGLISERIDA PADA TIKUS OBESITAS - Irma Santi; Rizqi Nur Azizah; Mu’ammar Mu’ammar (As-Syifaa Jurnal Farmasi, 2018)
Common purslane (Portulace Oleracea L.) has a compound of omega-3, flavonoid and ascorbic acid with the activity in decreasing triglyceride levels. This study aimed to determine the minimum dose of ethanol extract of common purslane against the decrease of triglyceride levels of obese mice. It used 18 rats fed high-calorie diet (HCD) for 30 days. The obese rats were devided into 6 groups consisting of group I of negative controls (Na.CMC ), group II of positive control (gemfibrozil®), group III,IV,V,VI provided the ethanol extract of common purslane (EECP) with 25 mg/kgBW, 50 mg/kgBW, 75 mg/kgBW, 100 mg/kgBW. Afterwards, 14 days of therapy were given and still fed a high-calorie (HCD). The measurement of triglyceride levels is performed before induction (early). After induction , and after therapy. The data of the study were analized by percentage decrease of each test group. The result show that the EECP groups of 75 mg/kgBW was the minimum dose in lowering triglyceride levels with a decrease of 16,49 %.